2019
DOI: 10.3390/molecules24244501
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ginseng Anti-Diabetic Studies

Abstract: Ginseng is one of the most valuable and commonly used Chinese medicines not only in ancient China but also worldwide. Ginsenosides, also known as saponins or triterpenoids, are thought to be responsible for the beneficial effects of ginseng. In this review, we summarize recent publications on anti-diabetic studies of ginseng extracts and ginsenosides in cells, animals, and humans. It seems that the anti-diabetic effect of ginseng is positive for type 2 diabetic patients but has no significant impact on prediab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 68 publications
0
58
0
1
Order By: Relevance
“…In general, saponins, which were isolated from ginseng that has been proven significant antidiabetic activity. The mechanism of these components in antidiabetic treatment is to moderate the enzyme activity [ 50 , 60 ] to influence glucose metabolism and control insulin secretion [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…In general, saponins, which were isolated from ginseng that has been proven significant antidiabetic activity. The mechanism of these components in antidiabetic treatment is to moderate the enzyme activity [ 50 , 60 ] to influence glucose metabolism and control insulin secretion [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…Intervention studies in humans and animals have demonstrated that ginseng extracts and ginsenosides improve insulin sensitivity [47,48]. In vitro studies have also shown their modulatory effects on PPARγ, a nuclear receptor for anti-diabetic drugs, and the expression of its downstream target genes [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…Panax quinquefolius saponin (PQS), extracted from the leaves of ginseng, [ 111 ] has been reported to have pharmacological activity, including kidney protection, [ 112 ] antioxidative, [ 113 ] anti‐inflammation, [ 114 ] and hypoglycemic [ 115 ] effects. The protective effects of PQS against cisplatin‐induced cardiotoxicity were investigated in ICR mice.…”
Section: Protective Effects Of Natural Compounds Against Cytotoxic Drmentioning
confidence: 99%